KERAGAMAN Liriomyza spp. (DIPTERA;AGROMYZIDAE) YANG BERASOSIASI DENGAN BERBAGAI JENIS TANAMAN SAYURAN DAN TUMBUHAN LIAR DI TIMOR LESTE - Americo Alves Brito; I Wayan Supartha; I Putu Sudiarta (Journal of Agricultural Science and Biotechnology, 2016)
Field research was conducted in Distrit Ainaro, Aileu, Bobonaro, Dili and Ermera. Maintenance and identification of Liriomyza and parasitoids was conducted in laboratory of Plant Protection, Department of Plant Protection of Agriculture, Ministry of Agriculture and fisheries Timor Leste. The purpose of the study to determine the diversity and abundance of leaf miner populations of Liriomyza spp. and parasitoids on vegetable crops in Timor Leste. The results showed there were two Liriomyza species, associated with host plants in the lowlands to the highlands of Timor Leste. The Both species are Liriomyza sativae (Blanchard) and Liriomyza sp. (Blanchard) The highest population abundance of Liriomyza sativa on tomatoes, red beans, Cucurbita maxima dan Cucumis sativus. while the highest populations of Liriomyza sp. on petsay crop.